Observing photons in space : a guide to experimental space astronomy - Pauluhn, Anuschka; Culhane, J. Len; Timothy, J. Gethyn; Wilhelm, Klaus; Zehnder, Alex (ISSI Scientific Report Series ;, 2013)
An ideal resource for lecturers, this book provides a comprehensive review of experimental space astronomy. The number of astronomers whose knowledge and interest is concentrated on interpreting observations has grown substantially in the past decades; yet, the number of scientists who are familiar with and capable of dealing with instrumentation has dwindled. All of the authors of this work are leading and experienced experts and practitioners who have designed, built, tested, calibrated, launched and operated advanced observing equipment for space astronomy. This book also contains concise information on the history of the field, supported by appropriate references. Moreover, scientists working in other fields will be able to get a quick overview of the salient issues of observing photons in any one of the various energy, wavelength and frequency ranges accessible in space. This book was written with the intention to make it accessible to advanced undergraduate and graduate students.